Dimensionamento e análise da viabilidade da implantação de um sistema de microgeração fotovoltaica no Câmpus da UTFPR - Pato Branco - Stanqueviski, Lucas Luan da Fonseca (2016)
The solar energy photovoltaic is one of the most promising ways of renewable energy, once that – in the last decade – it has had an enormous increase worldwide through several governmental benefits, which motivated the installation of these systems, beyond of the cost-cutting of technology. In this context, this paper has as main objective accomplish a study about the sizing and an analysis about the viability of the implantation of a photovoltaic microgeneration system at the UTFPR – Pato Branco campus. The paper presents, initially, the photovoltaic technology state of art and development perspectives. In the sequence are present the main differences between isolated systems and connected systems to the electrical grid, being the latter configuration used in the proposed project. Besides, the chosen area for the allocation of the photovoltaic panels was determined considering technician and economic aspects related to the existing structure. To finalize, the paper still presents a simplified analysis about the economic and financial viability of the proposed system.